Comparison and Evaluation of Research Results in Women With Osteoporosis Period of Menopause (Eurasian Medical Research Periodical, 2023)
It should be noted that the level of timely diagnosis and treatment of systemic osteoporosis remains low. Each of the existing systematic diagnostic methods is aimed at determining the structure or function of bone tissue. It should be remembered that in clinical practice, a comprehensive examination of patients is relatively rare. In addition, in 50% of cases, osteoporosis occurs without obvious symptoms (Franke Yu., Runge G., 1995; Rozhinskaya L.Ya., 1998). Thus, in modern dentistry, the study of the effect of general osteoporosis on the organs of the oral cavity, the prevention of complications of the disease remains an urgent problem.